Berdamai dengan Hutan; Memberdayakan Kelompok Tani Dusun Sodong Ponorogo sebagai Agen Substitusi Pangan - Hendra Afiyanto (LP2M of Institute for Research and Community Services - UIN Walisongo, 2018)
The cutting of the poverty chain is done through providing entrepreneurial insight to the farmer groups that is an agricultural sector of cassava super that is able to provide bigger income to improve the economic level of the community. The development of entrepreneurial spirit will automatically cut the unemployment class, the working class of Sodong village Sampung sub-district Ponorogo regency. Later, with the emergence of many cassava super entrepreneurs, people's income will increase. The increasing income of the community is related to the increasing level of education of the younger generation. If the level of education has begun to increase, the poverty rate will gradually be reduced in the following year. This paper concludes that Sodong farmers which are actually part of a social group, in a community stigmatized as looters and forest destroyers. Even if it is empowered with a structured plan, this stigma can be eliminated. The farmers should be able to be used as an agent to socialize various processed cassava products as food crops to replace rice. Pemotongan mata rantai kemiskinan bisa dilakukan melalui pemberian wawasan kewirausahaan kepada kelompok tani bahwa ada sektor pertanian singkong dengan varietas gajah yang mampu memberikan income lebih untuk meningkatkan taraf ekonomi masyarakat. Berkembangnya jiwa wirausaha akan secara otomatis memangkas kelas pengangguran, kelas buruh masyarakat KT dsn. Sodong, kec. Sampung. Nantinya dengan banyak munculnya wirausahawan singkong gajah maka pendapatan masyarakat meningkat. Peningkatan pendapatan masyarakat berelasi dengan meningkatnya tingkat pendidikan generasi muda. Jika tingkat pendidikan sudah mulai mengalami peningkatan maka secara perlahan angka kemiskinan ditahun berikutnya sedikit dapat dikurangi. Tulisan ini menyimpulkan bahwa kelompok tani Dusun Sodong yang notabene merupakan bagian dari kelompok sosial, di masyarakat distigma sebagai penjarah dan perusak hutan. Padahal jika diberdayakan dengan rencana terstruktur maka stigma ini dapat dihilangkan. Kelompok tani tersebut seharusnya bisa dimanfaatkan sebagai agen untuk memasyarakatkan berbagai hasil olahan singkong sebagai tanaman pangan pengganti beras.